CSC684 - Game Programming / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
This course aims to teach students to design, develop and implement computer games that involve real-time, event-driven and multimedia programming techniques. Topics in this course include graphics, game engines, motion control, narrative in games, game interfaces, and artificial intelligence. At the end of this course, students will be able to develop a computer game applying proven game design and software engineering principles.